Growth response and nutrient utilization of Clarias gariepinus fingerlings exposed to Dichlorvos - Abdulwakil Saba; Ramota Tahir; Emeka Ndimele; Musa Ibrahim (Hasanuddin University, 2021)
Organophosphate pesticides exert neurotoxicity by inhibiting acetylcholinesterase (AChE) in animals. Early-life exposure to agrochemicals affects growth performance and survival of non-target aquatic resources. In this study, lethal and growth responses of Clarias gariepinus fingerlings exposed to Dichlorvos (2, 2-dichlorovinyl dimethyl phosphate or DDVP), commonly known as ‘Sniper’ or ‘Ota-piapia’ in Nigeria were evaluated. The acute toxicity test shows that the mortality recorded after every 24 hours was concentration-dependent. The median lethal concentration (LC50) of DDVP on C. gariepinus fingerlings at 24, 48, 72 and 96 hours post-exposure (hpe) were 3.30 mg/L (3.197 to 3.441; R2 = 0.964), 2.30 mg/L (1.844 to 2.518; R2 = 0.866), 2.27 mg/L (2.117 to 2.373; R2 = 0.959) and 1.88 mg/L (0.7704 to 2.211; R2 = 0.74), respectively. After a feeding trial experiment on post-exposed fingerlings, there was no significant difference (p > 0.05) between the feed intake of the control and DDVP exposed groups. Except for protein intake, significant differences (p < 0.05) were found in the growth and nutrient utilization parameters. The findings of this study reveal that C. gariepinus fingerlings could recover after acute exposure to Dichlorvos at different concentrations.